2009
DOI: 10.1021/jm901233u
|View full text |Cite
|
Sign up to set email alerts
|

Potent Inhibitors of β-Tryptase and Human Leukocyte Elastase Based on the MCoTI-II Scaffold

Abstract: MCoTI-II is a member of a class of microproteins known as cyclotides that possess a macrolactam-cystine knot scaffold imparting exceptional physiological stability and structural rigidity. Modification of residues in the active loop and engineered truncations have resulted in MCoTI-II analogues that possess potent activity against two therapeutically significant serine proteases: beta-tryptase and human leukocyte elastase. These results suggest that MCoTI-II is a versatile scaffold for the development of prote… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
127
0
4

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 126 publications
(132 citation statements)
references
References 26 publications
1
127
0
4
Order By: Relevance
“…This observation is consistent with recent studies which demonstrated that grafting sequences as long as sixteen amino acid residues into loop 6 does not alter the disulfide bond connectivity within MCoTI [29]. Moreover, the MCoTI-ll scaffold has been engineered to bind to a range of protein targets including HMD2 [29], beta-tryptase, human leukocyte elastase and matriptase [16,27,30,31], suggesting that the framework itself has plasticity to accommodate different sequences. However, introducing the Sortase A recognition sequence into other loop regions within the framework might pose a problem and hence would need to be carefully assessed on a case-by-case basis.…”
Section: Resultssupporting
confidence: 89%
“…This observation is consistent with recent studies which demonstrated that grafting sequences as long as sixteen amino acid residues into loop 6 does not alter the disulfide bond connectivity within MCoTI [29]. Moreover, the MCoTI-ll scaffold has been engineered to bind to a range of protein targets including HMD2 [29], beta-tryptase, human leukocyte elastase and matriptase [16,27,30,31], suggesting that the framework itself has plasticity to accommodate different sequences. However, introducing the Sortase A recognition sequence into other loop regions within the framework might pose a problem and hence would need to be carefully assessed on a case-by-case basis.…”
Section: Resultssupporting
confidence: 89%
“…The elastase inhibitory potency of synthetic compounds was determined by Thongyoo et al, 2009 method with some changes. The quantity of free p-nitroaniline, that was hydrolyzed by the action of elastase from the substrate (N-succinyl-Ala-Ala-Ala-p-nitroanilide) was quantified by calculating the absorbance at 410 nm.…”
Section: Elastase Inhibition Activity Assaymentioning
confidence: 99%
“…In a more recent study, the same authors also generated inhibitors of the serine proteases β-tryptase and human leukocyte elastase (HLE) using the backbone of MCoTI-II [96]. β-Tryptase is implicated in allergic and inflammatory disorders, and HLE has been associated with respiratory and pulmonary disorders.…”
Section: Designing Cyclotides With Novel Biological Activitiesmentioning
confidence: 99%
“…β-Tryptase is implicated in allergic and inflammatory disorders, and HLE has been associated with respiratory and pulmonary disorders. Replacing the P1 residue in loop 1 produced several MCoTI-II mutants (K6A and K6V) with activity against HLE with K i values of 20-30 nM [96] and K i values against trypsin above 1 μM. Removal of the SDGG peptide segment in loop 6 yielded a ß-tryptase inhibitor with a K i ≈ 10 nM without significantly altering the three-dimensional structure as determined by NMR [96].…”
Section: Designing Cyclotides With Novel Biological Activitiesmentioning
confidence: 99%
See 1 more Smart Citation